2005
DOI: 10.1038/sj.embor.7400449
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐talk between the mechano‐gated K 2P channel TREK‐1 and the actin cytoskeleton

Abstract: TREK-1 (KCNK2) is a K 2P channel that is highly expressed in fetal neurons. This K þ channel is opened by a variety of stimuli, including membrane stretch and cellular lipids. Here, we show that the expression of TREK-1 markedly alters the cytoskeletal network and induces the formation of actin-and ezrin-rich membrane protrusions. The genetic inactivation of TREK-1 significantly alters the growth cone morphology of cultured embryonic striatal neurons. Cytoskeleton remodelling is crucially dependent on the prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
121
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 127 publications
(129 citation statements)
references
References 22 publications
6
121
1
Order By: Relevance
“…S2 A and B). Consistent with previous studies (18,25), we found that HA-TASK3 pulled down GFP-TASK3 or GFP-TASK1 with similar efficiency (Fig. S2C).…”
Section: Resultssupporting
confidence: 92%
“…S2 A and B). Consistent with previous studies (18,25), we found that HA-TASK3 pulled down GFP-TASK3 or GFP-TASK1 with similar efficiency (Fig. S2C).…”
Section: Resultssupporting
confidence: 92%
“…3 B, D, and E). This observation supports the idea that desensitization does not arise from the cytoskeleton, because that is expected to be similar after transfection with different channels [although see our previous report showing that cytoskeleton structure can be coupled to specific K 2P channel expression (25)]. The average P 1/2 value determined by fitting pressure-effect curves with a Boltzmann function (see Fig.…”
Section: Resultssupporting
confidence: 87%
“…The effect of patch excision is actually mimicked by latrunculin A treatment in the cellattached configuration (see ref. 25 and Fig. 6B).…”
Section: Resultsmentioning
confidence: 75%
See 1 more Smart Citation
“…Similar observations have also been made on mechanosensitive channels of known molecular identity. For example, treatment with latrunculin, another such agent, greatly enhances the suction-induced current through TREK-1-expressed in COS cells (85). Mutating β-spectrin, which links the membrane to the cytoskeleton, reduces the force needed to pull membrane tether from cultured touch-receptor neurons of the worm with an atomic force microscope (86).…”
Section: Accessoriesmentioning
confidence: 99%